Prevalence of Venous Thromboembolism in Critically Ill Patients With Coronavirus Disease 2019: A Meta-Analysis - Wu, Changgang; Liu, Yunlong; Cai, Xiangjing; Zhang, Wenming; Li, Yongjie; Fu, Chunsheng (Frontiers in Medicine, 2021)
Background: Accumulating evidence suggests that coronavirus disease 2019 (COVID-19) is associated with hypercoagulative status, particularly for critically ill patients in the intensive care unit. However, the prevalence of venous thromboembolism (VTE) in these patients under routine prophylactic anticoagulation remains unknown. A meta-analysis was performed to evaluate the prevalence of VTE in these patients by pooling the results of these observational studies. Methods: Observational studies that reported the prevalence of VTE in critically ill patients with COVID-19 were identified by searching PubMed and Embase database. A random-effects model was used to pool the results by incorporating the potential heterogeneity. Results: A total of 19 studies with 1,599 patients were included. The pooled results revealed that the prevalence of VTE, deep venous thrombosis (DVT) and pulmonary embolism (PE) in critically ill patients with COVID-19 was 28.4% (95% confidence interval [CI]: 20.0-36.8%), 25.6% (95% CI: 17.8-33.4%) and 16.4% (95% CI: 10.1-22.7%), respectively. Limited to studies, in which all patients received routine prophylactic anticoagulation, and the prevalence for VTE, DVT and PE was 30.1% (95% CI: 19.4-40.8%), 27.2% (95% CI: 16.5-37.9%) and 18.3% (95% CI: 9.8%-26.7%), respectively. The prevalence of DVT was higher in studies with routine screening for all patients, when compared to studies with screening only in clinically suspected patients (47.5% vs. 15.1%, P<0.001). Conclusion: Critically ill patients with COVID-19 have a high prevalence of VTE, despite the use of present routine prophylactic anticoagulation.